The Role of the Indonesian Language in Communication and Education within the Baduy Dalam Community - Lina Marliana Dewi; Nirmala Nirmala (International Forum of Researchers and Lecturers, 2025)
The Indonesian language holds a strategic role as a unifying national language as well as the medium of instruction in education. However, this role has not been fully internalized within indigenous communities such as the Baduy Dalam tribe, which is known for its strong adherence to tradition and the use of the Baduy dialect of Sundanese in daily life. This study aims to reveal the role of the Indonesian language in communication and education within the Baduy Dalam community and to analyze how the national language is adopted amidst the strong local culture. This research employs a qualitative method with data collection techniques including in-depth interviews, participatory observation, and document studies conducted within the Baduy Dalam community in Lebak Regency, Banten. The results indicate that the Indonesian language is beginning to be used in educational contexts, especially in formal schools around the Baduy area, although its use remains limited in everyday interactions among community members. Proficiency and understanding of Indonesian are more dominant among the younger generation who receive formal education. The social implications of these findings include the opening of access to broader information and knowledge for the Baduy Dalam people, but also present challenges in preserving local language and cultural values. This study recommends educational approaches based on local wisdom to ensure that the role of the Indonesian language progresses in harmony with the preservation of the Baduy Dalam cultural identity.